Perancangan Game "Galah Asin" untuk Memperkenalkan Budaya Tradisional Jawa Barat - Rama Dwissa Wiana; Intan Rizky Mutiaz; Alvanov Zpalanzani Mansoor (Wimba : Jurnal Komunikasi Visual, 2012)
Galah Asin is a cultural product that is gradually displaced along with the changing time. This is due to the discontinuation of cultural inheritance that made the previous generation. Traditional childrenâs games as a product of cultural tradition are not registered, nor socialized to the succeeding generation. The advancement of various electronic media also distract the public, especially children, who tend to leave traditional games that are not considered practical, because they often require a game field. PC gaming is one of the popular media among urban community that can be used as a medium for introducing traditional games in a digital form. Designing game of Galah Asin for children 6-12 years on the PC platform aims to reintroduce Galah Asin as West Java traditional game through more interesting and fun media. Interesting and fun because by playing, players are not only obtaining verbal information, but also, but game is also capable of displaying simulation that is roughly equal to the original game, although not replace the experience of playing the original game. The methodology of design / research conducted was descriptive qualitative, research with problem solving orientation. The methods adopted including data searching, data processing, designing games (pre-production), game development (production), testing the game (post-production), and then draw conclusions from the findings. From this research, Galah Asin game application is produced which ready for socialization or can be developed further. We came to the conclusion that the existence of digital games can be used as a more interesting and fun medium of publication of information about traditional games. Thus, information about the traditional culture would be preserved, even in the demands of sustainable era.